Factors of Formation of Community Centers in Small Towns - Khamrakulov, O.; Kamilova, M.; Aminova, Rukhshona (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses the conditions for the formation of public centers in small towns and the internal planning structure of public centers.